Efecto de Diferentes Dosis de extractos vegetales en el cultivo del Tomate (Lycopersicon escu/entum) y en el control de Meloidogyne sp. en Cacatachi - Bartra Coral, Roció Julisa (2003)
In an experiment carried out in a soil Ultisol of frank texture, located in the district of Cacatachi County and Department of San Martín; different dose of vegetable extracts (Lonchocarpus sp., Clibadíum sp. and Chenopodium sp.) they were applied directly on neck and roots of seedling and Tomate plants with the purpose of controlling present gills in the roots caused by nematodes of the gender Meloidogyne sp.. The results revealed highly significant differences in the carried out evaluations. The study demonstrated that the vegetable extracts influenced in the development of the different parts of the plants increasing (longitude of the roots. floral cushions and quality of fruits) and diminishing (height, floral branches). Likewise they diminished the number of gills causad by Meloidogyne sp. the yields were superior with regard to the witness.